Pengembangan Sistem Sensor berbasis Tekanan Udara untuk Deteksi Kontak Kaki Robot - Dwi Prasetyo, Wahyu Agung; Darmawan, Adytia; Dewanto, Raden Sanggar; Alfathdyanto, Khairurizal (AI Society & STMIK Indonesia, 2025)
Legged robot is preferred choice for travesing uneven terrain. Robot leg can be positioned dynamically to achieve better locmotion. Detection of the leg contact point became more of essential part for the unpredictable course. The common method by deploying resistive force sensor provides a binary condition of whether the leg has touches surface. This paper explores the possibility of implementing air pressure sensor on a sensor system to provide more information at robot leg contact point. Air pressure sensor can provide a more wide and continuous range of value that fluctuates along the contact rate of the leg. Verification of the study uses single leg part of dog-type quardruped. The sensor testing gave the output value with average error of 1,3%. The pressure sensor provides readings at around ± 40ms with maximum readable pressure of 1,5 kPa.